Perancangan Interior Fasilitas Dolanan Edutainment untuk Anak Usia 4-12 Tahun di Surabaya - Safira Caroline Christina (Intra, 2017)
This facility was designed based on the need for recreation spaces such as entertainment and education facilities for children in Surabaya. Reality shows that facilities like this are still limited and many children cannot enjoy the experience of it. This design is different and comes with a new look that is packed with the new concept and the culture of East Java. The aim of this design is to accommodate and educate children about the culture of East Java.